Use of spectral indices and photosynthetic parameters to evaluate the growth performance of hydroponic tomato at different salinity levels - Khalid A. Al-Gaadi; Ahmed M. Zeyada; Elkamil Tola; Rangaswamy Madugundu; Mohamed K. Edrris; Omer Mahjoop (PLoS ONE, 2025)
Conventional methods for measuring plant physiological parameters are expensive and time-consuming, and this has promoted the use of optical and sensing techniques. Therefore, this study was conducted to investigate the effect of salinity on the performance of hydroponic tomato plants, based on optical and sensing techniques (i.e., spectral indices and photosynthetic parameters), as well as fruit yield. Four spectral vegetation indices-VIs (Moisture Stress Index “MSI”, Canopy Response Salinity Index “CRSI”, Normalized Difference Nitrogen Index “NDNI” and Green Leaf Index “GLI”) were calculated using spectral measurements collected from tomato plant leaves. Also, four photosynthetic parameters (Net photosynthetic rate “PN”, Water use efficiency “WUE”, Transpiration rate “Tr” and Total stomatal conductance “Gs”) were measured from the same tomato plant leaves. Measurements were recorded for tomato plants grown under three salinity levels (Salinity-1; 2.5 dS m-1), (Salinity-2; 4.0 dS m-1), and (Salinity-3; 6.5 dS m-1) at different growth stages represented by days after transplantation (DAT), as 35 DAT (vegetative stage), 50 DAT (1st cluster flower stage), 60 DAT (3rd cluster flower stage), 75 DAT (fruit development stage) and 85 DAT (fruit ripening stage). Results showed that tomato plants were significantly affected by the imposed salinity treatments. Where, tomato plants treated with salinity-1 was healthier compared to salinily-3 treated plants. This has been concluded from the results of the studied VIs, where the highest mean values of MSI (0.543) and CRSI (0.779) were associated with salinity-3, along with low values of GLI (0.353) and NDNI (0.220), indicating high salinity stress. However, the highest mean values of both NDNI (0.232) and GLI (0.386) were observed for salinity-1, indicated healthy condition. It also proven with the studied photosynthetic parameters, with the highest mean values of PN (9.8 µmol CO2 m-2 s-1),Gs (0.117 mmol H2O m-2 s-1) and Tr (2.236 mmol H2O m-2 s-1) were associated with salinity-1, While the lowest mean values of PN (8.3 µmol CO2 m-2 s-1), Gs (0.102 mmol H2O m-2 s-1) and Tr (1.902 mmol H2O m-2 s-1) were recorded for the plants treated with salinity-1. Moreover, the total tomato fruit yield also decreased significantly at salinity-3 compared to salinity-1.